THE CORRELATION BETWEEN READING HABIT AND GRAMMAR MASTERY AT ENGLISH EDUCATION DEPARTMENT BATCH 2012 OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Risa Nurfadhilah (PBI 15 UMY 018, 2015)
*18 Reading is important in English teaching and learning process since it gives important contribution to the development of the productive skill, namely speaking and writing. Moreover, reading is essential for students to improve their writing skill especially in improving their grammar mastery. However, not all students of English Enducation Department (EED) of Universitas Muhammadiyah Yogyakarta (UMY) have high motivation to read, and high English grammar mastery. This has raised a question whether these two things are significantly correlated. This study aims to know (1) the students ’reading habit at EED UMY, (2) the students’ grammar mastery at EED UMY, and (3) the correlation between reading habit and grammar mastery at EED UMY students. Data were collected from 81 students of batch 2012, selected from the EED undergraduate students of third years. The researcher used the questionnaire to measure reading habit. The students’ grammar mastery data was taken from the score of the Structure and Written Expression Section of TOEFL ® in International Language Testing Class. The data were analyzed using descriptive statistic and descriptive correlation processed in SPSS 20.0. The Pearson Product Moment correlation coefficient was used to see the correlation between reading habit and grammar mastery. The analysis of the data indicates that students’ reading habit was in the moderate level (28,4 – 36,6) in three indicators, and the students’ grammar mastery was in the moderate level (38,4 – 49,9). The finding shown that correlation p-value was 0,08 vii and the correlation between reading habit and grammar mastery r=0.945 (at 0.01 level, sig 2-tailed) meaning there is no significant correlation between reading habit and grammar mastery of EED UMY students’.